2009
DOI: 10.2134/jeq2008.0407
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Hygienic Barrier Efficiency of a Compact On‐site Wastewater Treatment System

Abstract: The long-term use of a filter-based, on-site wastewater treatment system increases nutrient discharge to receiving waters and may reduce its hygienic barrier efficiency. The main purpose of this research was to assess the hygienic barrier efficiency and the associated health risks of an on-site system that had exceeded its 5-yr design capacity with respect to phosphorus (P) removal. The system was investigated for bacteria and virus removal and assessed with respect to potential health risks in relation to reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…For example, Heistad et al . () reported that the median P I‐annual of rotavirus for exposure through direct contact during irrigation with treated sewage water and consumption of lettuce was 10 − 1 to 10 − 2 , which is similar to that found in the present study for rotavirus (10 − 1 to 10 − 3 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, Heistad et al . () reported that the median P I‐annual of rotavirus for exposure through direct contact during irrigation with treated sewage water and consumption of lettuce was 10 − 1 to 10 − 2 , which is similar to that found in the present study for rotavirus (10 − 1 to 10 − 3 ).…”
Section: Discussionsupporting
confidence: 89%
“…as suggested by Heistad et al . (). This equation allowed estimation of concentration of pathogens considering the faecal input only from the infected persons: CP in nontreated greywater=FL×PD×YI×ET×false(1+URfalse)×NIP365×Qwhere CP is the concentration of the pathogen (CFU or PFU l −1 ), PD is pathogen density in the faeces, also referred to as excretion rate of pathogen in faeces (CFU or PFU g −1 ), YI is number of infection episodes per year per person, ET is the pathogen excretion time (days), UR is the underreporting ratio of disease incidence and NIP is the number of infected persons (Table ).…”
Section: Methodsmentioning
confidence: 97%
“…effluent filters, to guarantee effective removal of pathogens and other pollutants (Heistad et al, 2009). For example, in a study to assess removal of phosphorus, bacteria, and viruses by an onsite system containing a septic tank, a pressure-dosed vertical flow biofilter, and an upflow filter unit with lightweight clay aggregates a progressively decreased phosphorus removal by the filters in the end of and after a 5-year design capacity was exceeded (Heistad et al, 2009). In addition, there was a substantial decrease in the removal efficiency of E. coli during three years of operation, from 5.6 log 10 to 2.6 log 10 reduction.…”
Section: Figure 3 Septic Tank Showing Three Distinct Layers (Scum (Omentioning
confidence: 99%
“…The long-term use of a filter-based, on-site wastewater treatment system increases nutrient discharge to receiving waters and may reduce its hygienic barrier efficiency. In Norway, based on removal of bacteriophages, it was estimated high RVA infection risk (>1/10,000 per annum) for children that accidentally ingest 1-2 mL of the effluent of a septic tank receiving wastewater from single households (Heistad et al, 2009).…”
Section: Water-based Sanitation -Onsitementioning
confidence: 99%